Effectiveness of Implementation of Adiwiyata School Program - Darwis, Muh.; Haerul, Haerul; Khaeruddin, Faizah; Sufriadi, Sufriadi (Program Pascasarjana Universitas Negeri Makassar, 2024)
This research looks to assess how well the Adiwiyata School Program works in fostering environmental education and sustainable behaviors in students. The main focus is on measuring how students engage and change their behaviors due to involvement in the program. To achieve this, we will need data on what students know, how they feel, and what they do regarding environmental matters, in addition to insights from teachers and program leaders. The research uses a mixed-methods strategy, involving quantitative surveys to assess shifts in student knowledge, views, and actions, along with qualitative input from teachers and program leaders. The findings show a notable rise in students' awareness of environmental issues and their proactive actions, with 75% of participants saying they better understand these issues and 65% showing changes in their waste management and conservation habits. These results highlight the program's importance in building a culture of sustainability in schools, linking environmental education to students' everyday behaviors. The relevance of this study goes beyond just schools, as it points out the crucial link between environmental health and public wellness. By illustrating how educational programs can help create responsible future citizens, this study recommends practical approaches for incorporating environmental health into broader public health plans. The implications of these results support the idea of adopting similar educational programs nationwide, suggesting that such initiatives can lead to significant behavioral changes that enhance community health and environmental sustainability, ultimately benefiting both the population and the planet.